1999
DOI: 10.1076/jcen.21.2.149.929
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Memory in Children with Traumatic Brain Injury

Abstract: This study aimed to investigate whether implicit memory is preserved in children with traumatic brain injury (TBI). A fragmented picture-completion procedure (Snodgrass, Smith, Feenan, & Corwin, 1987) was used to compare implicit and explicit memory of 12 children with severe long-term TBI and 12 controls, matched for age and gender. On the implicit memory task, both the TBI and control groups were found to show significant priming. In addition, the extent of priming for the two groups was not found to be diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
(24 reference statements)
2
14
0
1
Order By: Relevance
“…The patients claimed that the speed of psycho-motor activity (e.g., speech and writing) drastically slowed following the injury. These introspective data of Abe (2000a;2000b) are consistent with the previous evidences (scholastic ability: Ewing-Cobbs et al, 1998; event memory: Arciniegas, Olincy, Topkoff, McRae, Cawthra, Filley, Reite, & Adler, 2000;Cooke & Kausler, 1995;Shum, Jamieson, Bahr, & Wallace, 1999;Shum, Valentine, & Cutmore, 1999;attention: Chan, 2001;Christodoulou, DeLuca, Ricker, Madigan, Bly, Lange, Kalnin, Liu, Steffener, Diamond, & Ni, 2001;Fenwick & Anderson, 1999;Leclercq, Couillet, Azouvi, Marliner, Martin, Strypstein, & Rousseaux, 2000;Tate, 1999).…”
supporting
confidence: 80%
“…The patients claimed that the speed of psycho-motor activity (e.g., speech and writing) drastically slowed following the injury. These introspective data of Abe (2000a;2000b) are consistent with the previous evidences (scholastic ability: Ewing-Cobbs et al, 1998; event memory: Arciniegas, Olincy, Topkoff, McRae, Cawthra, Filley, Reite, & Adler, 2000;Cooke & Kausler, 1995;Shum, Jamieson, Bahr, & Wallace, 1999;Shum, Valentine, & Cutmore, 1999;attention: Chan, 2001;Christodoulou, DeLuca, Ricker, Madigan, Bly, Lange, Kalnin, Liu, Steffener, Diamond, & Ni, 2001;Fenwick & Anderson, 1999;Leclercq, Couillet, Azouvi, Marliner, Martin, Strypstein, & Rousseaux, 2000;Tate, 1999).…”
supporting
confidence: 80%
“…Similarly, the infrequent reporting of implicit memory loss in day-to-day functioning tends to support the results of laboratory-based studies of visual priming and procedural learning, which found that children with moderate-to-severe TBI were unimpaired on these tasks compared with control groups [14,15]. Taken together, the parents' reports of impaired explicit and generally-preserved implicit memory in their children tend to demonstrate the ecological validity of a theorized functional dissociation between these two types of memory.…”
Section: Discussionmentioning
confidence: 59%
“…Taken together, the parents' reports of impaired explicit and generally-preserved implicit memory in their children tend to demonstrate the ecological validity of a theorized functional dissociation between these two types of memory. This dissociation was first noted by Cohen and Squire [57] and has been reported consistently since in adults [21][22][23] and children with TBI [14,15]. This functional distinction suggests an anatomical dissociation (i.e.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This finding illustrates the benefits of the Gollin test as a particularly good instrument for measuring perceptual learning, priming, and memory (Shum et al 1999; Warrington and Weiskrantz 1968ösee section 1). In the present study, we have shown that the influence of spectral similarity between the figure and mask becomes smaller with repeated exposures.…”
Section: Discussionmentioning
confidence: 70%